2012
DOI: 10.1152/ajpcell.00062.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell BK channels interact with RACK1, and PKC increases its expression on the cell surface by indirect phosphorylation

Abstract: Large conductance (BK) calcium activated potassium channels (Slo) are ubiquitous and implicated in a number of human diseases including hypertension and epilepsy. BK channels consist of a pore forming α-subunit (Slo) and a number of accessory subunits. In hair cells of nonmammalian vertebrates these channels play a critical role in electrical resonance, a mechanism of frequency selectivity. Hair cell BK channel clusters on the surface and currents increase along the tonotopic axis and contribute significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
(82 reference statements)
2
17
0
Order By: Relevance
“…The BK-␣ subunit is the pore-forming unit of the BK channel (Knaus et al, 1994), and it has been shown that there is a direct relationship between BK channel regulation of neuronal excitability and the level of BK-␣ subunits at the surface membrane (Shruti et al, 2012;Chen et al, 2013;Cox et al, 2014). Therefore, we examined the possibility that METH-mediated suppression of neuronal activity is due to METH-induced reduction of the BK-␣ subunit level at the plasma membrane.…”
Section: Meth Reduces Membrane Levels Of Bk-␣ Subunits Via a Protein mentioning
confidence: 99%
See 4 more Smart Citations
“…The BK-␣ subunit is the pore-forming unit of the BK channel (Knaus et al, 1994), and it has been shown that there is a direct relationship between BK channel regulation of neuronal excitability and the level of BK-␣ subunits at the surface membrane (Shruti et al, 2012;Chen et al, 2013;Cox et al, 2014). Therefore, we examined the possibility that METH-mediated suppression of neuronal activity is due to METH-induced reduction of the BK-␣ subunit level at the plasma membrane.…”
Section: Meth Reduces Membrane Levels Of Bk-␣ Subunits Via a Protein mentioning
confidence: 99%
“…For example, activation of BK channels has been shown to enhance the excitability of adrenal chromaffin cells (Solaro et al, 1995;Lovell and McCobb, 2001), CA1 hippocampal pyramidal cells (Gu et al, 2007), and parasympathetic cardiac motoneurons in the nucleus ambiguus . Similarly, enhancement of BKchannel currents has been linked to neuronal hyperexcitability and epilepsy in cortical neurons (Brenner et al, 2005;Lorenz et al, 2007;Shruti et al, 2008;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations